Cultural semiotics analysis of two artworks by Oswaldo Guayasamín : Análisis semiótico-cultural de dos obras de Oswaldo Guayasamín - Rodríguez Álvarez, Ada; Guamán Remache, Bélgica; Guambi Chasipanta, Heidi (situArte, 2021)
In this study we analyzed, from a cultural semiotic point of view, the social and cultural significance of two artworks by the Ecuadorian painter Oswaldo Guayasamín, one of the best proponents in Ecuador’s plastic arts field. For the analysis, Iuri Lotman’s theory reflections and support were used, as well as the technique of hermeneutic exegesis for the commentary of the intentional pictorial sample selected for the study. As a result of the research, we conclude that: a) Iuri Lotman’s theory allows analyzing the semiosphere of select pictorial artworks and reveal a relationship between the artwork of the artist and the contextual reality of his time; b) Guayasamín’s artwork has a strong cultural value and can be considered a kind of criticism of the disadvantaged life of the humble and battered people.